Occupational Lung Diseases - Tushar Kapoor (NMO Journal)
Despite federally mandated safety standards, occupational lung disease remains one of the most common work-related injuries. Inhaled dust can result in a range of tissue injury in the lung and can lead to significant respiratory insufficiency causing death.